Effects of school environments on student risk-behaviours: evidence from a longitudinal study of secondary schools in England. Issue 6 (23rd February 2019) - Bonell, Chris; Beaumont, Emma; Dodd, Matthew; Elbourne, Diana Ruth; Bevilacqua, Leonardo; Mathiot, Anne; McGowan, Jennifer; Sturgess, Joanna; Warren, Emily; Viner, Russell M; Allen, Elizabeth
Abstract : Background: The theory of human functioning and school organisation proposes that schools with rigid 'boundaries' (weaker relationships), for example, between staff and students, or learning and broader development, engender weaker student school commitment and sense of belonging, particularly among disadvantaged students, leading to greater involvement in risk-behaviours. Existing studies provide some support but rely on a proxy exposure of 'value-added education' and have not explored effects by disadvantage. Methods: We used longitudinal data from English secondary schools from the control arm of a trial, assessing school-level measures of rigid boundaries, and student commitment and belonging at age 11/12, and student risk-behaviours at age 14/15. Results: Our direct measures were more strongly associated with risk-behaviours than was value-added education. School-level rigid boundaries were associated with increased alcohol use and bullying. Student belonging was more consistently associated with reduced risk-behaviours than was student commitment. Some school effects were greater for students from disadvantaged subgroups defined in terms of poverty, ethnicity and family structure. Conclusion: Our results provide direct support for the theory of human functioning and school organisation and suggest a sense of belonging in school might be particularly protective factor among secondary school students. School effects on risk are generally stronger among disadvantaged students as theorised. Trial registration number: ISRCTN10751359